Structural and Functional Characterization of Phosphatidylinositol-Phosphate Biosynthesis in Mycobacteria. Issue 18 (21st August 2020) - Belcher Dufrisne, Meagan; Jorge, Carla D.; Timóteo, Cristina G.; Petrou, Vasileios I.; Ashraf, Khuram U.; Banerjee, Surajit; Clarke, Oliver B.; Santos, Helena; Mancia, Filippo
Abstract: In mycobacteria, phosphatidylinositol (PI) acts as a common lipid anchor for key components of the cell wall, including the glycolipids phosphatidylinositol mannoside, lipomannan, and lipoarabinomannan. Glycolipids in Mycobacterium tuberculosis, the causative agent of tuberculosis, are important virulence factors that modulate the host immune response. The identity-defining step in PI biosynthesis in prokaryotes, unique to mycobacteria and few other bacterial species, is the reaction between cytidine diphosphate–diacylglycerol and inositol-phosphate to yield phosphatidylinositol-phosphate, the immediate precursor to PI. This reaction is catalyzed by the cytidine diphosphate–alcohol phosphotransferase phosphatidylinositol-phosphate synthase (PIPS), an essential enzyme for mycobacterial viability. Here we present structures of PIPS from Mycobacterium kansasii with and without evidence of donor and acceptor substrate binding obtained using a crystal engineering approach. PIPS from Mycobacterium kansasii is 86% identical to the ortholog from M. tuberculosis and catalytically active. Functional experiments guided by our structural results allowed us to further characterize the molecular determinants of substrate specificity and catalysis in a new mycobacterial species. This work provides a framework to strengthen our understanding of phosphatidylinositol-phosphate biosynthesis in the context of mycobacterial pathogens. Graphical abstract: Unlabelled Image Highlights: Previous PIPS structures have not captured a complete view of substrate binding. We present structures of catalytically active PIPS from Mycobacterium kansasii . One structure of Mk PIPS presented shows evidence of substrate binding. Functional assays measured effect of key residue mutations on PIPS activity. These structures add to the current knowledge of PIPS and its enzyme family.